2021
DOI: 10.1063/5.0055127
|View full text |Cite
|
Sign up to set email alerts
|

Domain structure evolution during alternating current poling and its influence on the piezoelectric properties in [001]-cut rhombohedral PIN-PMN-PT single crystals

Abstract: Extensively studied PMN-PT and PIN-PMN-PT crystals with compositions close to the morphotropic phase boundary possess excellent piezoelectric characteristics. Recently developed alternating current treatment enhances the piezoelectric performance even further. Here, we demonstrate the results of studying the domain structure evolution by direct optical imaging during polarization reversal in [001]-oriented PIN-PMN-PT single crystals of rhombohedral phase during alternating current poling (ACP). The main types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Dr. Xifa Long and Dr. Chao He's team of FJIRSM CAS reported a series of significant studies of ACP PIN-PT with high Curie temperature (T C ), 66) various waveforms, 67) thickness effect 74) and PYbN-PMN-PT ACP with combining DCP. 68) Recently, Ushakov et al 69) reported that cross-like domain structure (CDS) was found to be undesirable for the application. ACP proved to be effective in reducing the CDS fraction as a result of the growth of lens-shaped domains attributed to the 71°switching.…”
Section: Principles and Research History Of Acpmentioning
confidence: 99%
“…Dr. Xifa Long and Dr. Chao He's team of FJIRSM CAS reported a series of significant studies of ACP PIN-PT with high Curie temperature (T C ), 66) various waveforms, 67) thickness effect 74) and PYbN-PMN-PT ACP with combining DCP. 68) Recently, Ushakov et al 69) reported that cross-like domain structure (CDS) was found to be undesirable for the application. ACP proved to be effective in reducing the CDS fraction as a result of the growth of lens-shaped domains attributed to the 71°switching.…”
Section: Principles and Research History Of Acpmentioning
confidence: 99%
“…Just recently, Ushakov et al reported that cross-like domain structure (CDS) was found to be undesirable for the piezoelectric application. 44) The ACP proved to be effective in reducing the CDS fraction as a result of the growth of lensshaped domains attributed to the 71°switching. The interaction of cross-like and lens-shaped domains was proposed as a key mechanism for improving the piezoelectric properties by ACP treatment.…”
Section: Resultsmentioning
confidence: 96%
“…[ 21 ] Similar results were also obtained in other studies, [ 22 ] including other relaxor‐ferroelectrics such as PIN–PMN–PT. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[21] Similar results were also obtained in other studies, [22] including other relaxorferroelectrics such as PIN-PMN-PT. [23] Part of the reason for the conflicting results observed in the literature lies in the limitations of DW density characteri zation methods. Typical experimental methods used to char acterize domains can be classified into electromechanical (piezoresponse force microscopy (PFM)), [11] optical (polarized light microscopy (PLM), [21] and diffractionbased (Xray diffrac tion (XRD)) [24] ) methods.…”
Section: Introductionmentioning
confidence: 99%